Book Review Nicole S. Young, Food Photography: From Snapshots to Great Shots (Second Edition) - Afif, Fuadi; Hermawan, Hary (Gastronomy and Culinary Art, 2025)
This book review discusses Food Photography: From Snapshots to Great Shots (Second Edition) authored by Nicole S. Young and published by Peachpit Press in 2016. The book provides a comprehensive guide to the technical and creative aspects of food photography, ranging from fundamental photographic principles, lighting, and food styling to composition, digital editing, and strategies for online presence. The review highlights the book’s practical strengths, such as its accessible explanations, systematic structure, and visual examples that effectively demonstrate key techniques. The author’s integration of technical guidance with digital marketing strategies makes the book highly relevant to the current creative economy and the growing role of food photography in social media and gastronomy-related industries. However, the book’s limitations lie in its strong focus on specific photographic equipment and the lack of cultural or critical perspectives on food representation. Despite these limitations, the book is considered a valuable reference for students, novice photographers, culinary practitioners, and academics seeking to enhance their understanding of food photography and its role in the digital era.